중소벤처기업의 CEO리더십이 관계금융을 매개로 하여 경영성과에 미치는 영향에 관한 연구 - 황연(Yeon Hwang); 유왕진(Wang Jin Yu); 엄기수(Kee Soo Eum) (대한경영학회지, 2018)
중소벤처기업부 자료에 의하면 2014년 기준으로 우리나라 중소벤처기업은 전체 사업체수의 99.9%를 차지하고 있으며, 전체 종사자수의 87.8%가 중소벤처기업에서 일하고 있다. 한편 중소벤처기업 CEO의 리더십 유형과경영성과의 관계는 수많은 선행연구의 관심사였다. 최근 중소벤처기업에 대한 금융지원과 관련하여 관계금융이 주목받고 있다. 본 연구는 국내 대표적인 중소벤처기업 전문은행인 K은행과 여신거래중인 중소벤처기업을 대상으로 CEO 리더십이 관계금융을 매개변수로 하여 경영성과에 미치는 영향에 관한 실증 연구이다. 연구 결과를 요약하면 다음과 같다. 첫째, 중소벤처기업의 CEO리더십 유형 중 거래적 리더십과 변혁적리더십은 모두 재무성과 및 비재무성과에 정(+)의 영향을 미치는 것을 확인하였다. 이는 거래적 리더십이경영성과에 부정적 영향을 미친다는 일부의 선행연구와 달리 거래적 리더십도 경영성과 향상에 기여함을입증하였다. 둘째, 거래적 리더십과 관계금융의 관계분석에서 관계적 요소는 부(-)의 영향을 미치지만, 금융적요소는 정(+)의 영향을 미치고 있음을 확인하였다. 변혁적 리더십은 관계금융의 두 요소에 정(+)의 영향을미친다. 이는 교환관계를 중시하는 거래적 리더십을 가진 리더는 은행과의 거래에서 거래기간, 자금조달 집중도, 보유금융상품수 등에 있어서 주고받기식의 거래성향이 강함을 시사하고 있다. 셋째, 관계금융의 관계적요소는 거래적 리더십과 경영성과 사이에서 매개효과가 없는 것으로 확인되었으며, 변혁적 리더십과 경영성과사이에서는 정(+)의 매개효과가 있음을 확인하였다. 특히 변혁적 리더십과 재무성과 사이에서는 완전매개효과를 보였다. 넷째, 관계금융의 금융적 요소는 거래적 리더십과 변혁적 리더십이 모두 경영성과 사이에서정(+)의 매개효과를 확인하였다. 특히 거래적 리더십과 비재무성과 사이에서, 변혁적 리더십과 재무성과 사이에서 완전매개 효과를 보였다. 이는 중소벤처기업이 주거래은행과의 금융거래 편의, 정성적 신용평가 이점, 경영컨설팅 수혜 등 관계금융의 금융적 요소는 거래은행의 중소벤처기업에 대한 일종의 금융서비스를 강조한개념으로서 거래적 리더십을 가진 리더도 경영성과에 기여함을 시사하고 있다. 또한, 관계금융은 중소벤처기업 CEO의 리더십 유형이 변혁적 리더십일 때 재무성과 향상에 더 큰 영향력을미치는 것으로 나타났다. 그리고 중소벤처기업 CEO가 거래적 리더십 유형일 때 비재무성과를 향상시키기위해서는 관계금융의 금융적 요소를 강화해야 함을 시사하고 있다. 이와 같이 본 연구는 기존 선행연구에서 다루어지지 않은 중소벤처기업 CEO리더십과 경영성과 사이의관계금융의 매개효과 영향관계를 입증함으로써 중소벤처기업 경영성과 향상에 기여하고자 하였다. According to statistics supported by Ministry of SMEs and Startups, 2014, medium-sized venture enterprises consist of 99.9% of companies in Korea, employing 87.8% of workers. The relationship between medium-sized venture enterprise CEO’s type of leadership and management performance had been an issue in many preceeding studies. Recently, financial supporting on small and medium-sized venture enterprises via relationship banking is receiving attention. The purpose of this empirical study is to find out the effect of CEO leadership on the management performance mediated by the relationship banking in the small and medium-sized venture enterprises as a loan customer in a bank in Korea. The results of the study are as follows. First, In the relationship between CEO leadership of the SMEs and management performance, CEO leadership showed a significant positive effect(+) on the management performance. It proved transactional leadership also contributes to management performance improvements, opposing several preceeding studies. Second, In the relationship between transactional leadership and relationship banking, we verified that a significant negative effect(-) on the relational factor of relationship banking, but, a significant positive effect(+) on the financial factor of relationship banking. It suggests that transactional leadership likely to show reciprocal exchange in business relationship length, concentration of financing, number of financial products in business, in relationship with bank. Third, We verified that the relational factor of relationship banking has no mediating effect between transactional leadership and management performance. However, it showed a positive mediating effect(+) between transformational leadership and management performance. Especially, the relational factor of relationship banking showed a perfect mediating effect between transformational leadership and financial performance. Fourth, We verified that the financial factor of relationship banking has a positive mediating effect(+) between CEO leadership and management performance. In particular, the financial factor of relationship banking showed a perfect mediating effect between transactional leadership and non-financial performance, between transformational leadership and financial performance. Therefore, this study tried to verify the effect on management performance not only in transformational leadership but also transactional leadership among the CEO leadership type in SMEs. We found that relationship banking clearly influences the financial performance of transformational leadership as well. In addition, this study suggests that when SME’s CEO has transactional leadership, we must strengthen the financial factor of relationship banking to improve non-financial performance. Thus, the results of the present study demonstrate the effect of CEO leadership on the management performance mediated by the relationship banking in the small and medium-sized venture enterprises which has not been covered in the previous research using SMEs as a adjust parameter. And, We verified that transactional leadership has a positive effect on financial and non-financial performance in the small and medium-sized venture enterprise. Thus, this study aims to conribute to management performance improvements of SMEs, proving mediating effect of relationship banking between SMEs CEO leadership nad management performance, uncovered in previous studies. KCI Citation Count: 2